Omega-6/Omega-3 and PUFA/SFA in Colossoma macropomum Grown in Roraima, Brazil - Antonio Alves Melho Filho; Hamilton Hermes Oliveira; Ricardo Carvalho Santos (Orbital: The Electronic Journal of Chemistry, 2013)
In this study was evaluated the fatty acids composition of tambaqui (Colossoma macropomum) fillet, fish species cultivated in Roraima State, Brazil. For the extraction of tambaqui oil was used Sohxlet device and then it was methylated. The oil  was identified using a gas chromatograph and were identified 24 acids and these were divided into characteristic groups such as: saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFA) and series fatty acids omega-6 and omega-3. The ratios obtained were PUFA/SFA and omega-6/omega-3. The results of chromatographic analysis were subjected to tests by variance ANOVA and multiple comparisons of Tukey at 5%. The ratios omega-6/omega-3 and PUFA/SFA showed values ​​of 8.58 and 0.75 respectively.